Sources, methods, and the violence of insurgency in Northern Ireland - Kowalski, RC (Oxford University Press, 2023)
The study of violence perpetrated by non-state groups is a burgeoning field of research. Across the disciplines scholars debate the character and impact of political violence. This chapter will introduce the various research methods employed to examine the disparate actions of violent individuals or groups during contemporary and past insurgencies, civil wars, or terrorist campaigns. It will explore the debate that persists among researchers concerning methodological best practice, using the violence perpetrated by the Provisional Irish Republican Army (PIRA) between 1969 and 1998 as a case study. Studies of every scale, scope, and methodological approach—qualitative and quantitative—have distinct strengths and merits; but they also have limitations. Studies that rely on a single research method or limited pool of evidence may, therefore, produce findings that are misleading without further qualification. This chapter argues that a mixed-method approach can potentially minimize the impact of the shortcomings of either qualitative or quantitative research. But the accuracy of claims based on academic research will always be subject to the quality of the sample of evidence selected and critical analysis that is employed to interrogate it. Accordingly, it is researchers’ awareness of and transparency regarding the specific limitations of their work that is of paramount importance.